Association Between Anemia and Cerebral Venous Thrombosis: Case–Control Study. Issue 10 (October 2015) - Coutinho, Jonathan M.; Zuurbier, Susanna M.; Gaartman, Aafke E.; Dikstaal, Arienne A.; Stam, Jan; Middeldorp, Saskia; Cannegieter, Suzanne C.
Abstract : Background and Purpose—: Anemia is often considered to be a risk factor for cerebral venous thrombosis (CVT), but this assumption is mostly based on case reports. We investigated the association between anemia and CVT in a controlled study. Methods—: Unmatched case–control study: cases were adult patients with CVT included in a single-center, prospective database between July 2006 and December 2014. Controls were subjects from the control population of the Multiple Environmental and Genetic Assessment of Risk Factors for Venous Thrombosis (MEGA) study. Anemia was defined according to World Health Organization criteria: nonpregnant women hemoglobin <7.5 mmol/L, pregnant women <6.9 mmol/L, and men <8.1 mmol/L. We used logistic regression analysis, adjusting for age, sex, malignancy, oral contraceptive use, and pregnancy/puerperium. Results—: We included 152 cases and 2916 controls. Patients with CVT were younger (mean age, 40 versus 48 years) and more often women (74% versus 53%) than controls. Anemia was more frequent in cases (27.0%) than in controls (6.5%; P <0.001). Anemia was associated with CVT, both in univariate analysis (odds ratio, 5.3; 95% confidence interval [CI], 3.6–7.9) and after adjustment for potential confounders (adjusted odds ratio, 4.4; 95% CI, 2.8–6.9). Hemoglobin as a continuous variable was inversely associated with CVT (adjusted odds ratio per 1 mmol/L change 0.53; 95% CI, 0.42–0.66). Stratification by sex showed a stronger association between anemia and CVT in men (adjusted odds ratio, 9.9; 95% CI, 4.1–23.8) than in women (3.6; 95% CI, 2.1–6.0). Conclusion—: Our data suggest that anemia is a risk factor for CVT.